Iowa statewide May count, Allamkee County, Fred Lesher, May 14, 1994 - Lesher, Fredet al (1994)
An annotated list of birds sighted by Fred Lesher and six others. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of Spring 1994. Plustek - flatbed